The Synergistic Effects of Anxiety and Cerebral Hypoperfusion on Cognitive Dysfunction in Older Adults with Cardiovascular Disease - Alosco, Michael L. (J Geriatr Psychiatry Neurol, 2014)
OBJECTIVES: Anxiety is a risk factor for cardiovascular disease (CVD) and is associated with neurocognitive outcomes. The effect of anxiety on brain perfusion in a CVD population has yet to be examined and no study has investigated the interactive effects of anxiety and cerebral perfusion on cognition. METHODS: 55 older adults with CVD completed the Beck Anxiety Inventory (BAI) and underwent arterial spin labeling to quantify cortical perfusion and thickness. Participants were administered the Mini Mental State Examination(MMSE) and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). RESULTS: Reduced perfusion predicted poorer cognition and decreased cortical thickness. Higher anxiety score predicted worse memory performance and decreased frontal perfusion. Frontal lobe hypoperfusion combined with increased BAI scores exacerbated poorer MMSE performance. CONCLUSIONS: Higher anxiety may exacerbate the effects of cerebral hypoperfusion on cognitive impairment. Longitudinal studies are needed to confirm our findings, and determine whether anxiety treatment improves neurocognitive outcomes in CVD.